Interaction between the root-feeding beetle, Longitarsus bethae (Coleoptera: Chrysomelidae) and the root-knot nematode, Meloidogyne javanica (Nematoda: Heteroderidae): Implications for the biological control of Lantana camara L. (Verbenaceae) in South Africa - Musedeli, Jufter (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2019)
Plants often are simultaneously attacked by several herbivores that can affect each other's performance, and their interaction may affect their host plant fitness. The current study was conducted to determine the interaction between the root-feeding beetle, Longitarsus bethae Savini & Escalona (Coleoptera: Chrysomelidae) and a root-knot nematode, Meloidogyne javanica (Treub) Chitwood (Tylenchida: Heteroderidae), with implications for the biological control of Lantana camara L. (Verbenaceae) in South Africa. The studies were conducted under quarantine conditions at the Agricultural Research Council-PHP, Roodeplaat, Pretoria, South Africa. Specifically, the study determined; (i) whether root damage by the flea beetle enhanced infection by M. javanica, (ii) whether L. camara roots infected with the nematode enhanced the performance of the beetle, (iii) whether single or combined effect of the two organisms (i.e. L. bethae and M. javanica) had an overall effect on the growth and biomass of their shared host, L. camara, and (iv) the susceptibility of 10 L. camara varieties that are commonly found in South Africa to M. javanica. The study found that galling on the roots of L. camara by the nematode occurs at the highest inoculation of 300 eggs of L. bethae per plant, and no galling occurred at inoculation of 200 eggs per plant and below. The findings also showed that L. bethae performed better on M. javanica-infected than on healthy L. camara roots, and that more L. bethae adult progeny with slightly bigger body size emerged from M. javanica-infected, than from healthy plants. Fresh weight (galls) of plant roots from treatments where both species (i.e., L. bethae and M. javanica) were combined was significantly higher than that from plants infected with the nematode only, suggesting that the combination of both species induces more galling than the nematode does alone. The above-ground dry biomass was significantly lower both in combined and M. javanica only treatments, than in L. bethae only treatment. The study also found that selected L. camara varieties were infected with M. javanica, albeit at varying degrees of infection. Among the 10 L. camara varieties, Orange Red OR 015 was the most susceptible. Other susceptible varieties included Light Pink 009 LP, Total Pink 021 TP and Dark Pink 018 DP, and these, together with variety Orange Red OR 015, constituted 40% of the L. camara varieties evaluated in the current study. Fifty percent of the varieties displayed slight to moderate susceptibility to M. javanica, while 10% displayed lack of susceptibility. The study concluded that the symbiotic relationship between L. bethae and M. javanica was mutual, resulting in increase in the fitness of the beetle. The combined herbivory by L. bethae and M. javanica was also found to be additive on one of the most common varieties of L. camara in South Africa, and therefore co-infestation by both species might enhance the biological control of this weed in South Africa. The study further concluded that the suitability of some invasive L. camara cultivars such as Light Pink 009 LP and Orange Red 015 OR for M. javanica, might also contribute towards biological control of this weed in South Africa, particularly in areas where the two herbivores species co-exist.
Keywords: Insect-plant relationships; Insects -- Host plants; Flea beetles; Symbiosis; Longitarsus; Chrysomelidae; Lantana camara -- Biological control -- South Africa; Heteroderidae; Root-knot nematodes; Weeds -- Biological control -- South Africa